The aqueous extract of Gerrardanthus macrorhizus caudex enhanced doxorubicin activity in MCF-7 human breast cancer cells - Sari Haryanti; Yuli Widiyastuti; Slamet Wahyono (Universitas Gadjah Mada, 2018)
Gerrardanthus macrorhizus (GM) caudex, is traditionally used in cancer therapy by the Tetun people in Belu District, East Nusa Tenggara Province, Indonesia, where it is known as “akar batu”. This study aimed to explore the cytotoxic effects of G. macrorhizus caudex aqueous extract, as well as its combination with doxorubicin, on MCF-7 cells. Also investigated were the possible mechanisms of interaction through cell cycle progression and apoptosis induction. Single treatments of 5–320 µg/mL of the extract showed morphological alterations in MCF-7 cells, but did not show any cytotoxic effect. Combining the extract with doxorubicin resulted in a synergistic cytotoxic effect. Doxorubicin concentrations equivalent to 1/12, 1/8, and 1/5 fold of the IC50 combined with 20 µg/mL decreased viability to 48%. We then explored the combination effect of doxorubicin 0.4 µM with GM 5 and 20 µg/mL using a flow cytometer. A low concentration of the extract (5 µg/mL) combined with 0.4 µM of doxorubicin resulted in slight cell cycle modulation by G1, G2M arrested and apoptosis induction. The combination of doxorubicin and a higher concentration of the extract (20 µg/mL) did not show cell cycle modulation, and led to necrosis. Therefore, G. macrorhizus caudex at low concentrations has the potential to be developed further as a co-chemotherapeutic agent.